Faktor-Faktor yang Berhubungan dengan Kejadian Harga Diri Rendah Pasien Gangguan Jiwa - Fitri Wijayati; Titin Nasir; Indriono Hadi; Akhmad Akhmad (Poltekkes Kemenkes Kendari, 2020)
Low self-esteem is a negative self-evaluations that associated with feelings of being weak, helpless, hopeless, frightened, vulnerable, fragile, incomplete, worthless, and inadequate. The research objective was to determine the factors that associated with low self-esteem incidence of mental patients in mental hospital Southeast Sulawesi province in 2015. This type of research is analytic using cross sectional. The study population was all mental patients with low self-esteem in RSJ southeast Sulawesi province in 2015 the number of 171 people. A sample of 63 people, the sampling technique is purposive sampling, statistical test used was chi square test and phi. The results showed that the variables associated with the incidence of low self-esteem is a history of persecution physical, the loss of a nearby, family rejection, and repeated failure. Suggested for mental hospital institution providing education on the importance of the client’s family to provide supports and praise sentences clients who have low self-esteem to restore confidence lost clients.